Powerful or powerless? Beyond power and powerlessness: The Leipzig Leadership Model provides some answers - Timo Meynhardt; Manfred Kirchgeorg; Andreas Suchanek; Henning Zülch (Leadership, Education, Personality. An Interdisciplinary Journal, 2019)
Leadership is about more than simply wielding power. The Leipzig Leadership Model places the importance of consistently contributing to a greater good at the centre of the concept of leadership. The critical factor is what leaders use their power for and what they use as orientation in the process. In this article, we describe the model and its guiding idea. The model incorporates the conviction that, in a fundamentally uncontrollable world, it is important to remain capable of acting and develop an attitude whereby leaders define themselves through a value contribution rather than status, knowledge, or power.
Keywords: 330; Purpose; Entrepreneurial spirit; Responsibility; Effectiveness; Value contribution